Förster resonance energy transfer (FRET)-based small-molecule sensors and imaging agents. (22nd July 2020) - Wu, Luling; Huang, Chusen; Emery, Ben P.; Sedgwick, Adam C.; Bull, Steven D.; He, Xiao-Peng; Tian, He; Yoon, Juyoung; Sessler, Jonathan L.; James, Tony D.
Abstract : In this tutorial review, we will explore recent advances in the construction and application of Förster resonance energy transfer (FRET)-based small-molecule fluorescent probes. Abstract : In this tutorial review, we will explore recent advances in the construction and application of Förster resonance energy transfer (FRET)-based small-molecule fluorescent probes. The advantages of FRET-based fluorescent probes include: a large Stokes shift, ratiometric sensing and dual/multi-analyte responsive systems. We discuss the underlying energy donor–acceptor dye combinations and emphasise their applications for the detection or imaging of cations, anions, small neutral molecules, biomacromolecules, cellular microenvionments and dual/multi-analyte responsive systems.